(untitled) (Materiali di Estetica. Terza serie, 2016)
The essay takes up Neri’s article, Caravaggio e la scuola del silenzio, remembering how he allows the painting to remain silent, respecting its essential aphasia. However Neri, as a philosopher of art, cannot refrain from query and commenting paintings through language. In this case Neri remarks how Caravaggio falls into the oxymoron, on one side keeping the silent of painting, on the other interpreting human passions as an existentialist philosopher.